A Posteriori Error Estimates of the Galerkin Spectral Methods for Space-Time Fractional Diffusion Equations (Advances in Applied Mathematics and Mechanics, 2020)
In this paper, an initial boundary value problem of the space-time fractional diffusion equation is studied. Both temporal and spatial directions for this equation are discreted by the Galerkin spectral methods. And then based on the discretization scheme, reliable a posteriori error estimates for the spectral approximation are derived. Some numerical examples are presented to verify the validity and applicability of the derived a posteriori error estimator.